2021
DOI: 10.3390/microorganisms9010191
|View full text |Cite
|
Sign up to set email alerts
|

Core and Accessory Genome Analysis of Vibrio mimicus

Abstract: Vibrio mimicus is an emerging pathogen, mainly associated with contaminated seafood consumption. However, little is known about its evolution, biodiversity, and pathogenic potential. This study analyzes the pan-, core, and accessory genomes of nine V. mimicus strains. The core genome yielded 2424 genes in chromosome I (ChI) and 822 genes in chromosome II (ChII), with an accessory genome comprising an average of 10.9% of the whole genome for ChI and 29% for ChII. Core genome phylogenetic trees were obtained, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…V. mimicus is an emerging zoonotic gram-negative bacterial pathogen that can infect a wide range of fish species (Guardiola-Avila et al, 2021 ), including Siluriformes, Cypriniformes, and Perciformes (Elgendy et al, 2022 ), as well as crustaceans (Jiang et al, 2022 ), resulting in severe vibriosis. The disease has rapid onset, rapid progression, and high mortality that can reach 80–100% (Geng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…V. mimicus is an emerging zoonotic gram-negative bacterial pathogen that can infect a wide range of fish species (Guardiola-Avila et al, 2021 ), including Siluriformes, Cypriniformes, and Perciformes (Elgendy et al, 2022 ), as well as crustaceans (Jiang et al, 2022 ), resulting in severe vibriosis. The disease has rapid onset, rapid progression, and high mortality that can reach 80–100% (Geng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The internal reference genes are very important for transcriptional-level studies, and a good internal reference gene needs to meet a certain amount of expression and stable expression. The common internal reference genes selected for V. cholerae transcription were ompT ( vc0862 ) ( 15 ), rpoA ( vc2571 ) ( 16 , 17 ), gyrB ( vc0015 ) ( 18 , 19 ), thyA ( vc0675 ) ( 20 ), and recA ( vc0543 ) ( 21 ). Under all conditions, we found that the expression levels of these internal reference genes were not stable under specific conditions ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a phylogenetic analysis based on the core genome ( 9 ) ( Appendix ), the 2 Florida strains clustered within a single, well-supported clade consistent with their high similarity, indicating a very recent common origin ( Figure ). Although the maximum-likelihood tree of available V. mimicus sequences shows several independent lineages of strains sampled worldwide with no apparent geographic structure, the closest lineages to the Florida strains were clinical isolates from the United Kingdom, as well as clinical and environmental strains from the United States, albeit with no strong bootstrap support.…”
Section: The Studymentioning
confidence: 89%